2010
DOI: 10.1029/2010jb007402
|View full text |Cite
|
Sign up to set email alerts
|

Fission‐track thermochronology, vertical kinematics, and tectonic development along the western extension of the North Anatolian Fault zone

Abstract: We have investigated the low‐temperature history of pre‐Neogene basement areas adjacent to the western extension of the North Anatolian Fault zone (NAFZ) by apatite fission track thermochronology of 33 samples taken from Marmara island, Kapidag peninsula (both in the Sea of Marmara), Samothrake island, and Chalkidike peninsula (both in the North Aegean region). Together with already published apatite fission track data from 30 other sampling localities of the region, these data (63 in total) have been evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 94 publications
(261 reference statements)
1
18
0
Order By: Relevance
“…Using the same modeling approach and the samples GR117, GR126, GR132, and GR134 from Hejl et al . [], we calculated, for comparison, the thermal path of the lower Eocene Sithonia pluton from the southern edge of the Chalkidiki peninsula (see Figure for location). (bottom) The corresponding FT age (blue), mean track length (red), and kinetic parameter (green) predictions for the constrained and nonconstrained models are shown.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the same modeling approach and the samples GR117, GR126, GR132, and GR134 from Hejl et al . [], we calculated, for comparison, the thermal path of the lower Eocene Sithonia pluton from the southern edge of the Chalkidiki peninsula (see Figure for location). (bottom) The corresponding FT age (blue), mean track length (red), and kinetic parameter (green) predictions for the constrained and nonconstrained models are shown.…”
Section: Resultsmentioning
confidence: 99%
“…The cooling path crosses the high‐temperature limit of the apatite FT partial annealing zone (~120°C) at uppermost Cretaceous (between 62 and 70 Ma) and remains at temperature <50°C since the lower Eocene. Using the available geochronology data [ Hejl et al ., ] for a typical Lower Eocene pluton of the first magmatic pulse (Sithonia pluton from the southern tip of the Chalkidiki peninsula; Figure ) and the profile modeling technique described in a previous section, we can demonstrate that this pluton cooled to 50°C as early as lowermost Oligocene (~33 Ma), i.e., 10–15 Myr later than the surrounding basement rocks (Figure ). Thus, it can be concluded that none of the two magmatic pulses penetrating the Vertiskos Unit (Eocene and Oligo‐Miocene) were strong enough to cause regional thermal perturbations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, there are Eocene plutonic rocks of various shapes and sizes intruding into the pre-Paleocene units of the eastern Pontides, Sakarya, and Tavşanlı Zones in NW Anatolia (Harris et al, 1994;Köprübaşı and Aldanmaz., 2004;Topuz et al, 2005Topuz et al, , 2011Karacık et al, 2008;Ustaömer et al, 2009;Karslı et al, 2011;Altunkaynak et al, 2012;Ersoy and Palmer, 2013;Topuz and Okay, 2017). During Oligocene time a regional exhumation took place (Hejl et al, 2010;Cavazza et al, 2012) and the whole of the Pontides, except the westernmost part (northern and eastern part of the Thrace basin; Less et al, 2011;Okay et al 2019), was uplifted above sea level. Thus, the Eocene sediments represent the last marine deposits in most of the Pontides.…”
Section: Geological Context During the Late Cretaceous-eocene Intervamentioning
confidence: 99%
“…Here, the thermal sensitivity of (U‐Th‐Sm)/He and apatite FT systems to low‐temperatures between 40°–80°C and ∼60°–120° [e.g., Green et al , 1986; Farley , 2000] provides a unique perspective for fault dating. Most apatite based thermochronological estimate studies estimate fault ages indirectly by comparing the cooling histories of the foot and hanging wall sections across major faults [e.g., Ehlers and Farley , 2003; Redfield et al , 2005; Seiler et al , 2010; Hejl et al , 2010]. Past attempts to directly date heat transfer along faults by apatite FT and (U‐Th‐Sm)/He data were usually less successful.…”
Section: Introductionmentioning
confidence: 99%